LAPAROSCOPIC CHOLECYSTECTOMY–A COMPARISON BETWEEN OPEN VERESS NEEDLE TECHNIQUE - Khalid Hussain; Aurangzeb; Jovaria Masood (Pakistan Armed Forces Medical Journal, 2015)
Objective: To compare the open versus Veress needle method of producing pneumoperitoneum in laparoscopic cholecystectomy in terms of time required to induce pneumoperitoneum and to close the port site wounds. Study Design: Randomized clinical trial. Place and Duration of Study: Department of Surgery, Military Hospital, Rawalpindi from Aug 10, 2011 to Aug 10, 2012. Material and Method: One hundred and thirty patients between 27 and 60 years of age undergoing laparoscopic cholecystectomy during the study period were enrolled. Patients were divided into two equal groups by lottery method. Group A had pneumoperitoneum by open method and Group B by Veress needle. All surgeries were performed by the same surgical team by using standard four post technique. General Results: There were a total of sixty five patients in each group. Time required to create pneumoperitoneum ranged from 6.30 to 10.89 minutes in group A and 6 to 16.59 minutes in group B. Mean time to create pneumoperitoneum was 8.35 minutes in group A and 10.10 minutes in group B. Time spent on wound closure Conclusion: Open method to create pneumoperitoneum and to close port site wounds is less time consuming than veress needle method